2005
DOI: 10.1002/chin.200549109
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Catalyst for the Selective Hydrogenation of Furfural to Furfuryl Alcohol.

Abstract: Furfuryl Alcohol.-MCM-41 supported Cu/La-catalyst with high metal loading level and dispersion degree is prepared via a novel preparative method. The catalyst exhibits high activity and selectivity in the hydrogenation of furfural (I) to furfuryl alcohol (II). -(HAO, X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…A similar strategy was considered by Liu and coworkers, who doped a Cu/MCM-41 catalyst with La. 622 As a result, excellent conversion (98%) and selectivity (>99%) were obtained after 1 h of operation, probably because of the high electron-donating ability of La, which increased basicity and favored CO hydrogenation (Table 23, entry 19). However, after 8 h TOS, the catalyst lost 32% of its activity.…”
Section: Furan-2-yl(pyrrolidin-1-yl)methanone and Butylmentioning
confidence: 86%
See 3 more Smart Citations
“…A similar strategy was considered by Liu and coworkers, who doped a Cu/MCM-41 catalyst with La. 622 As a result, excellent conversion (98%) and selectivity (>99%) were obtained after 1 h of operation, probably because of the high electron-donating ability of La, which increased basicity and favored CO hydrogenation (Table 23, entry 19). However, after 8 h TOS, the catalyst lost 32% of its activity.…”
Section: Furan-2-yl(pyrrolidin-1-yl)methanone and Butylmentioning
confidence: 86%
“…Furfuryl alcohol is readily produced at the industrial level from the gas-phase reduction of furfural with hydrogen over Cu-based catalysts . Nevertheless, numerous recent reports in the primary literature were still devoted to the development of new catalysts for the gas-phase reduction of furfural into furfuryl alcohol in the presence of hydrogen. The main challenge of this reaction is related to the activity of the catalyst, which has to be finely tuned to reduce the aldehyde moiety of furfural only. Catalytic sites endowed with an overly high reducing ability are also prone to further reduce furfuryl alcohol ( 99 ) into 2-methylfuran ( 101 ), tetrahydro­furfuryl alcohol ( 102 ), and 2-methyltetra­hydrofuran ( 103 ) (Scheme ) as well as many other undesired compounds resulting from ring-opening.…”
Section: Upgrading Of Furansmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have studied the hydrogenation of furfural and reported kinetic data and/or kinetic models for the reaction [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A variety of different types of catalysts have been investigated for the reaction, including copper chromite, copper/sodium silicate and platinum catalysts.…”
Section: Reactions and Kineticsmentioning
confidence: 99%